The beautiful discourse of Sundanese women in Bandung City - Lusiana Peres Morelba; Aditya Candra Lesmana (Jurnal Sosiologi Dialektika, 2023)
Discourse is a system of thinking, ideas, or thoughts describing a culture or speech characteristic in a certain period. This article focuses on the discourse of beautiful Sundanese women in Bandung. This research is studied using Michel Foucault’s theory of discourse, with the archaeological method of knowledge to determine the discontinuity between one knowledge and another. Data collection techniques with in-depth interviews and documentation study. The results of this study indicate that the discussion of beautiful Sundanese women in the city of Bandung is first, beauty is not only judged by physical appearance, but the assessment of beauty is based on behavior and thoughts; second, women are considered beautiful when they are grateful, confident, find their unique beauty, and love themselves; and third, there is no the same physical standard, however, Sundanese women in Bandung expect healthy and clean facial skin. This study concludes that the discourse of beauty in Sundanese women was formed as a form of expression to maintain and love themselves and not about specific predetermined standards of beauty.